Pengaruh Brand Image, Lifestyle Dan Kualitas Produk Terhadap Minat Beli Smartphone IPhone (Studi Pada Mahasiswa Universitas Islam Malang Angkatan 2019) - Prasetio, Jony; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the influence of brand image, lifestyle and product quality on the interest in buying iPhone smartphones (Study on students of the Islamic University of Malang class of 2019). The type of research used is quantitative. The sampling method using the purposive sampling method is a sampling technique by taking into account certain criteria, namely active students of the Islamic University of Malang, the sample used in this study was 100 respondents obtained from the calculation of the slovin formula with a data collection model through a questionnaire. The data analysis method used in this study is multiple linear regression analysis, data processing using the SPSS program version 25 for windows. The results showed that in test F or simultaneously the variables brand image, lifestyle and product quality had a significant effect on buying interest. The results of the t test or partially show that the brand image variable has no effect on buying interest, lifestyle variables have a positive and significant effect on buying interest, product quality variables have a positive and significant effect on buying interest.  Keywords: Brand Image, Lifestyle, Product Quality, Buying Interest.